2016
DOI: 10.1017/neu.2016.48
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic abnormality in the right dorsolateral prefrontal cortex in patients with obsessive–compulsive disorder: proton magnetic resonance spectroscopy

Abstract: These findings would be helpful to understand the pathophysiology of OCD associated with the brain metabolic abnormalities in the right DLPFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…DLPFC is a critical area for cognitive control and executive processes, including response inhibition, behavioral flexibility, and orienting of attention. Previous studies reported brain metabolic abnormalities in OCD in the right DLPFC (Park et al ., 2017). Furthermore, clinical treatment using repetitive transcranial magnetic stimulation (TMS) targeting the right DLPFC has been shown to improve obsessive symptoms (Seo et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…DLPFC is a critical area for cognitive control and executive processes, including response inhibition, behavioral flexibility, and orienting of attention. Previous studies reported brain metabolic abnormalities in OCD in the right DLPFC (Park et al ., 2017). Furthermore, clinical treatment using repetitive transcranial magnetic stimulation (TMS) targeting the right DLPFC has been shown to improve obsessive symptoms (Seo et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies targeting cortical regions have found increased NAA/Cr[38] and decreased glutamate[44] in the medial PFC, decreased glutamate and increased myoinositol in the DLPFC,[48] and decreased NAA in the ACC,[4041] which increased after medication. [40] An older study had slightly different findings, with lower NAA concentration being found in the ACC in responders to selective serotonin reuptake inhibitors (SSRIs) with antipsychotic augmentation as compared to healthy controls, while no such differences were seen between SSRI responders and nonresponders.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…The pathophysiological feature of OCD, as revealed by fMRI studies, suggest that abnormal brain metabolites may be implied in OCDs. Abnormalities in brain metabolite concentrations in patients with OCD were investigated using proton MRS [167] , [168] , [169] , [170] . Among about ten detectable metabolites, glutamate, glutamine, and GABA are of particular interest, as they are involved in neurotransmission.…”
Section: Multimodal Imaging Data Fusion: Diseasesmentioning
confidence: 99%